DESAIN ULANG TEBAL LAPIS PERKERASAN LENTUR RUAS JALAN MAGELANG â YOGYAKARTA DENGAN MENGGUNAKAN PEDOMAN PERENCANAAN PERKERASAN TAHUN 2002 - , ISYANA YUVITA P ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Magelang â Yogyakarta road is a kind of Province Road that connecting Magelang city in Central Java Province and Yogyakarta city in Special District of Yogyakarta Province. This road ever had a problem with the increasing level of traffic activity in 2010 because of the eruption of Merapi Mountain that makes a lot of big truck comes to bring material from the Merapi Mountain. The designing of overlay using metode analisis komponen 1987 has already done and shows a big number of the width for the flexible pavement which means that the result is not effective. This analysis tried to redesigning the pavement road with the pavement design manual 2002 and comparing this two result. The result of calculation using pavement design manual 2002 shows a thinner width for the pavement layer, where the value of surface course is 14 cm and the width of base course is 25 cm with the capacity of traffic for 10 years is 35 Ã 106. Whereas the calculation using metode analisis komponen 1987 shows the width of surface course is 18 cm, the width of base course is 15 cm and the width of subbase course is 35 cm. The thinner result for the pavement layer also makes the cost for pavement construction cheaper.